Poppy and Max and the river picnic - Grindley, Sally; Gardiner, Lindsey (London : Orchard Books, 2008)
Poppy and Max set out to have a picnic by the river, and Max, who does not like long walks, makes her stop at a lot of places along the way.
"Orchard colour crunchies"--Cover p. [4].
School Library Journal.
School Library Journal, May 2009.
1.5
K-3
Keywords: Dogs -- Juvenile fiction; Picnics -- Juvenile fiction; Dogs -- Fiction; Picnics -- Fiction; Dogs -- Fiction; Picnicking -- Fiction